RENEWABLE ENERGY KOLABORATIF: PENGEMBANGAN SEKTOR GREEN ENERGY MELALUI PERTAMBANGAN YANG RAMAH LINGKUNGAN DI JAMBI DAN KALIMANTAN SELATAN - Nor Qomariyah; Hario Tamtomo; Zulfikri Akbar (LPPM Universitas Muhammadiyah Jambi, 2023)
Renewable energy which comes from various resources, such as sunlight, wind, rain, geothermal and biomass has a concept that is in line with the environmentally friendly green energy sector, which is synergized with the National Determine Contribution (NDC) achievements which are targeted to be achieved in 2030. Coal, as a mining sector, is still the main basis for the main supply of electrical energy in the domestic market where South Kalimantan is the 3rd national reserve, with a value of 3.67 billion tons. In relation to the NDC target, PT Banjar Bumi Persada (BBP) and PT Mitra Agro Semesta (MAS) located in Banjar Regency, South Kalimantan Province, are doing two main things to achieve the Coal to Clean Power synergy